The Prison and the Pinnacle - Milton, John, 1608-1674; Milton, John, 1608-1674; Rajan, Balachandra (Book collections on Project MUSE., 1973)
This volume brings together five papers read at the University of Western Ontario in 1971 to mark the tercentenary of the publication of Paradise Regained and Samson Agonistes. It commemorates what tradition has regarded as Milton's final poetic communication.